Investigation of Bufavirus and Parvovirus 4 in Patients with Gastro-Enteritis from the South-East of France - Francis Simo-Fouda; Laurence Thirion; Antoine Nougairède; Léa Luciani; Jean-Sélim Driouich; Paul Rémi Petit; Pascal Delaunay; Remi N. Charrel (Pathogens, 2021)
Bufavirus (BuV) and human parvovirus 4 (PARV4) belong to the Parvoviridae family. We assessed BuV and PARV4 DNA presence by real-time PCR analysis in stool, blood and respiratory samples collected in patients from Marseille and Nice, two large cities in the South-East of France. Bu-V DNA was detected in diarrheic stool samples from 92 patients (3.6% of 2583 patients), particularly men and adults, and patients from the nephrology and the infectious disease departments. Among the patients with a BuV-positive stool sample and for whom at least one blood sample was available (n = 30 patients), BuV DNA was detected also in 3 blood samples. In contrast, BuV DNA was not detected in any of the respiratory samples from 23 patients with BuV-positive stool. BuV detection rate was comparable in stool samples from patients with and without diarrhea. We did not detect PARV4 DNA in any of the stool specimens (n = 2583 patients). Our results suggest that PARV4 fecal–oral transmission is rare or non-existent in the South-East of France while BuV circulates with a relatively high rate in this area.